2010
DOI: 10.1016/j.bpj.2010.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Salicylate and a Terpenoid Plant Extract with Model Membranes: Reconciling Experiments and Simulations

Abstract: We investigate the effects of two structurally similar small cyclic molecules: salicylic acid and perillic acid on a zwitterionic model lipid bilayer, and show that both molecules might have biological activity related to membrane thinning. Salicylic acid is a nonsteroidal antiinflammatory drug, some of the pharmacological properties of which arise from its interaction with the lipid bilayer component of the plasma membrane. Prior simulations show that salicylate orders zwitterionic lipid membranes. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 49 publications
0
26
0
Order By: Relevance
“…Analogous problems for other FF were recently summarized by Khandelia et al 38 Given the importance of ions in biological systems, this is a matter of concern. However, due to the additive approximation in the FF, the treatment of ions is inherently problematic.…”
Section: Successes and Limitations Of C36mentioning
confidence: 80%
“…Analogous problems for other FF were recently summarized by Khandelia et al 38 Given the importance of ions in biological systems, this is a matter of concern. However, due to the additive approximation in the FF, the treatment of ions is inherently problematic.…”
Section: Successes and Limitations Of C36mentioning
confidence: 80%
“…Therefore, Khandelia et al (2010) evaluated the influence of ions (Na + , K + and TMA + ) in MD simulations [82]. Specifically, the effect of salicylate on a DMPC membrane depended on the ion type, and the authors suggested that the presence of Na + masked the disordering effect of the drug in the previous simulation [82]. Recently, Venable et al (2013) revised the Lennard-Jones radii of ions in the CHARMM force field to calibrate the results to the experimental NMR deuterium order parameters, which minimized possible artefacts caused by the binding of ions to the lipid headgroups [83].…”
Section: Accepted Manuscriptmentioning
confidence: 96%
“…Therefore, Khandelia et al (2010) evaluated the influence of ions (Na + , K + and TMA + ) in MD simulations [82]. Specifically, the effect of salicylate on a DMPC membrane depended on the ion type, and the authors suggested that the presence of Na + masked the disordering effect of the drug in the previous simulation [82].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Perillic acid is a terpenoid plant extract with antiinfective and anticancer properties, and is a small cyclic molecule structurally similar to salicylic acid. It is known to cause large-scale membrane thinning, a clearly possible antimicrobial activity through a membrane-lytic mechanism very close to that of AMPs (Khandelia et al, 2010). Indeed, also subproteins or subpeptides may be relevant to antimicrobial activity in silico prospection.…”
Section: Novel Amp Functions In Plantsmentioning
confidence: 99%